Valorization of Kraft lignin via alkaline and acid- mediated aerobic oxidation processes - Sutradhar, Shrikanta (My University, 2023)
Lignin is a complex heterogeneous aromatic compound derived from renewable plant biomass. Due to its aromatic backbone, it has grown interested in producing biochemicals and other polymeric applications. Depending on the sources and isolation methods, lignin has a wide range of functional groups, such as aliphatic/aromatic hydroxyl, carboxylic, sulphonic, and methoxyl groups, which make lignin chemically reactive for modification towards versatile applications. The main goals of this dissertation are categorized into two main sections. Firstly, KOH mediated aerobic oxidation of kraft lignin (KL) was performed to produce water-soluble KL that was applied as green fertilizer on maize seedlings and a mid-range cement plasticizer. Secondly, oxalic acid mediated oxidation of KL was conducted to produce aromatic biochemicals such as vanillin and vanillic acid. In this dissertation, the KL was aerobically oxidized in KOH solution to produce water-soluble anionic lignin. The oxidation reaction was optimized to achieve the maximum carboxylic acid groups and charge density. The XPS, 1 H-NMR, and 31 P-NMR confirmed the introduction of the carboxylic acid groups, while the FTIR, and HSQC-NMR confirmed the structural alterations in the oxidized lignin. The extensive degradations of the aromatic moieties (G-units) of lignin confirmed its ring openings during the alkaline oxidation. The fertilizing effects of the modified lignin were investigated on Zea mays seedlings. [...]
Keywords: Kraft lignin; Humic acid; Biomass; Alkaline aerobic oxidation; Humified lignin